Emergency Preparation and Green Engineering Tool - Whiteley, Clinton E (Kansas State University, 2008)
As our society continues to better prepare itself to address biological, radiological, chemical, and environmental emergencies, there is a need for better and more readily available emergency planning information for program managers and military/business personnel. An online hazardous materials and emergency planning tool for the Environmental Knowledge and Assessment Tool (EKAT: www.ekat-tool.com) would adequately fill that need. The proposed online Emergency Preparation and Green Engineering (EPGE) tool would provide the user with information regarding links to local emergency response teams and resources, guides for developing emergency plans and reports, Hazardous Materials (HAZMAT) training information, case studies to illustrate HAZMAT situations, and the ability to judge the environmental friendliness of chemicals. In this way it will serve as a means of facilitating and educating individuals for best responses in an organized fashion. In order to address their environmental responsibilities, public and private organizations are adopting Environmental Management Systems (EMS). The EPGE tool can be used in conjunction with Environmental Management Systems (EMS) to begin to address sustainability in a more practical setting. Currently the development of a comprehensive tool that identifies environmental, health, and safety concerns along with supplying relevant emergency data would be applicable to any business or organization. This tool will be available as an initial building block for the sustainability of the company. It can be used as a guide to better characterize and solve the environmental issues that could affect any business.
Keywords: Emergency response; Green engineering; Green chemistry; Hazardous waste operations and emergency response; Engineering, Chemical (0542)